Workplace chaplaincy: a literature review. Issue 1 (1st January 2018) - Wolf, Tanja; Feldbauer-Durstmüller, Birgit
Abstract: Interest in workplace spirituality has risen over the past few decades and it continues to garner increasing attention as evidenced by interdisciplinary scholarship and corporate interest. Workplace chaplaincy can be considered to be a special approach to spirituality in companies and therefore is described as a growing and concrete manifestation of workplace spirituality. Workplace chaplaincy can be called a phenomenon with a long history but partial scholarly study. This specialized manifestation of workplace spirituality has not yet received adequate academic attention and few empirical studies exist, but there are clear signs of emerging academic interest in this field of research. In this paper, we present an interdisciplinary systematic literature review focusing on the main topics in the available literature. As workplace chaplaincy is organized in different ways in different countries, the review aims to present diverse models of chaplaincy in various states. Furthermore, the question arises of whether workplace chaplaincy represents the real integration of spirituality or if it is just exploited by instrumentality, which means that workplace chaplaincy is solely regarded as an opportunity to improve the efficiency and performance of organizations.